1994 human resource management strategic plan of the South African Department of Labour - Madzivhandila, Thiambiwi Eunice (My University, 2001)
Refer to the document
Thesis (M. Dev.) -- University of Limpopo, 2001
Keywords: Human resource management; Strategic plan; Labour; Personnel management -- South Africa; Strategic planning -- South Africa